Penerapan Metode Simple Additive Weighting pada Sistem Rekrutmen Karyawan Berbasis Web - Amali, Lanto Ningrayati; Akbar, Muhammad Ilham; Pakaya, Nikmasari; Katili, Muhammad Rifai; Dwinanto, Arif; Padiku, Indhitya R. (Jambura Journal of Informatics, 2023)
The development of science and technology in the field of information system has resulted in improved organizational performance in managing information. This also applies to the employee recruitment system, which can be a solution to the employee recruitment process in an organization, where organizations can choose the right employees for their organization. Web-based employee recruitment systems are used to support the decision-making stage by identifying problems, selecting relevant data with Simple Additive Weighting (SAW) methods. This study aimed to design an employee recruitment system using the web-based SAW method. The prototype model system development method was used with the stages of communication, rapid planning, rapid design modeling, construction, and system submission. The data collection process was conducted through observation, interviews, and questionnaires. The result of this study is a web-based employee recruitment system that can input job vacancy data, applicant data, interview schedules, assessment data information, and assessment result reports. The results of the system evaluation using the System Usability Scale (SUS) obtained a value of 80, which shows the grade ranking of the SUS scores on the level of user acceptance in the acceptable category and grade scale category B, which means that the system has good quality and is easy to use by users. Berkembangnya ilmu pengetahuan dan teknologi di bidang sistem informasi mengakibatkan peningkatan kinerja organisasi dalam mengelola informasinya. Hal ini juga berlaku pada sistem rekrutmen karyawan yang dapat menjadi solusi dalam proses rekrutmen karyawan dalam sebuah organisasi, dimana organisasi dapat memilih sendiri karyawan yang tepat untuk organisasinya. Sistem rekrutmen karyawan berbasis web digunakan untuk mendukung tahap pengambilan keputusan dengan mengidentifikasi masalah, memilih data yang relevan dengan metode Simple Additive Weighting (SAW). Tujuan penelitian ini adalah merancang sistem rekrutmen karyawan dengan menggunakan metode SAW berbasis web. Metode yang digunakan adalah metode pengembangan sistem model prototype dengan tahapan komunikasi, perencanaan secara cepat, pemodelan perancangan secara cepat, konstruksi dan penyerahan sistem. Adapun proses pengumpulan data dilakukan dengan observasi, wawancara dan angket. Hasil penelitian ini adalah sistem rekrutmen karyawan berbasis web dimana sistem dapat menginput data lowongan pekerjaan, menginput data pelamar, membuat jadwal interview, menampilkan informasi data penilaian, serta menampilkan laporan hasil penilaian. Adapun hasil evaluasi sistem menggunakan System Usability Scale (SUS) didapat nilai sebesar 80 yang menunjukkan grade rangking of SUS scores pada tingkat penerimaan pengguna dalam kategori acceptable dan grade skala kategori B, yang artinya sistem memiliki kualitas yang baik dan mudah digunakan oleh pengguna.